Populist Rationality versus Representative Democracy (Cultura Económica, 2019)
Populism has been commonly considered opposed to liberalism, as a contrary phenomenon to institutionalism and democracy. This pejorative view of populism is redefined by Laclau and Mouffe, who argue that the participation of the people in this type of political systems is what ensures its democratic value, despite the fact that such participation is not done by conventional means. In this paper the principles upon which liberal democracy and populism are based, are presented briefly, in order to observe the criticisms Laclau and Mouffe made on both systems, studying its feasibility and the scope of their proposals.
Keywords: POPULISM; LIBERALISM; LACLAU; MOUFFE; DEMOCRACY